Primary pulmonary myoepithelial carcinoma in a child: An ambiguous entity - Kridis, Wala Ben (Lung India, 2015)
Primary myoepithelial carcinoma (MC) of the lung is exceedingly rare. We report here, to the best of our knowledge, the first pediatric case having primitive pulmonary MC. The originality of our case was the disappearance of the pulmonary opacity spontaneously, without any treatment. The difficulties in our case were the diagnosis of this rare entity and its subsequent treatment. In fact, given the rarity of these tumors, recommendations regarding chemotherapy or radiation, were difficult to formulate.